Hit the road [videorecording (DVD)] - Panahi, Panah; Panahiha, Pantea; Madjouni, Hassan; Sarlak, Rayan; Simiar, Amin; Jafari, Amin (Cinematographer); Yazdanian, Peyman (Kino Lorber, 2022)
It takes the tradition of the Iranian road-trip movie and adds unexpected twists and turns. It follows a family of four -- two middle-aged parents and their sons, one a taciturn adult, the other an ebullient six-year-old -- as they drive across the Iranian countryside. Throughout the trip, they bond over memories of the past, grapple with fears of the unknown, and fuss over their sick dog. Unspoken tensions arise and the film builds emotional momentum as it slowly reveals the furtive purpose of their journey. The result is a humanist drama that offers an authentic, raw, and deeply sincere observation of an Iranian family preparing to part with one of their own.